Pathogenesis of anemia in pregnant women with gestational diabetes mellitus - A. P. Zima; T. S. Prokhorenko; T. V. Saprina; N. N. Musina; V. V. Novitsky; A. N. Baykov (Бюллетень сибирской медицины)
The aim of the research was to establish the role of inflammation mediators and iron metabolism in the pathogenesis of various types of anemic syndrome in pregnant women with gestational diabetes mellitus (GDM).Materials and methods. 32 pregnant patients with GDM were examined; 14 of them had iron deficiency anemia, 18 – anemia of chronic diseases. The enzyme-linked immunosorbent assay was used to determine the concentration of IL-6, hepcidin and a soluble receptor for transferrin in the blood serum of pregnant women, the concentrations of C-reactive protein and transferrin were determined with the method of turbidimetry.Results. It was shown that women with GDM had higher IL-6 level compared to healthy pregnant women, and the concentration of IL-6 did not depend on the type of anemic syndrome. The C-reactive protein concentration was higher in patients with GDM and anemia of chronic diseases than in healthy pregnant women or in pregnant women with iron deficiency anemia. An analysis of iron metabolism markers in pregnant women with GDM established that patients with anemia of chronic diseases had higher hepcidin levels than women with iron deficiency anemia or healthy pregnant women.Conclusions. We established the heterogeneity of the anemic syndrome in pregnancy complicated by GDM. It was confirmed that GDM was accompanied by subclinical inflammation, which was more pronounced in anemia of chronic diseases. The research showed that the mechanism of development of anemia of chronic diseases involving the hepcidin protein was also realized in GDM, characterized by subclinical inflammation. The results indicate the importance of establishing the type of the anemic syndrome in pregnant women with GDM for effective therapeutic follow-up.